Strategic Analysis of Dive Tourism Development in Pramuka Island Thousand Islands Regency - Nada Yasmin; Atikah Nurhayati; Roffi Grandiosa Herman (Grouper, 2024)
This research was conducted on Pramuka Island, Panggang Island Village, North Thousans Island District, Thousans Island Administrative Regency, Daerah Khusus Jakarta Province. The implementation began in February 2024 and continued until March 2024. The purpose of this research aims to formulate strategies for developing dive tourism on Pramuka Island. The method used in this study is a case study on dive tourism in Pramuka Island, gathering both primary and secondary data. The sampling method employed is purposive sampling. Data analysis was performed using SWOT Analysis processed with Microsoft Excel. Based on the conducted research, the best strategy for developing dive tourism on Pramuka Island using SWOT Analysis is in quadrant I, which involves implementing an SO strategy or aggressive growth strategy with the coordinate points 0.33; 0.21, meaning leveraging strengths to capitalize on existing opportunities.